Extracorporeal life support in cardiovascular patients with observed refractory in-hospital cardiac arrest is associated with favourable short and long-term outcomes: A propensity-matched analysis. Issue 7 (November 2016) - Blumenstein, Johannes; Leick, Jürgen; Liebetrau, Christoph; Kempfert, Joerg; Gaede, Luise; Groß, Sebastian; Krug, Marcel; Berkowitsch, Alexander; Nef , Holger; Rolf, Andreas; Arlt, Matthias; Walther, Thomas; et al.
Aims: Extracorporeal life support (ECLS) has shown encouraging survival rates in patients with in-hospital cardiac arrest; however, its routine use is still controversial. We compared the survival of patients with in-hospital cardiac arrest receiving conventional cardiopulmonary resuscitation (CCPR) to that of patients with ECLS as an adjunct to cardiopulmonary resuscitation (ECPR). Methods: A total of 353 patients with in-hospital cardiac arrest (272 CCPR and 52 ECPR) were included in this retrospective, propensity score-adjusted (1:1 matched), single-centre study. Primary endpoints were survival at 30 days, long-term survival and neurological outcome defined by the cerebral performance categories score. Results: In the unmatched groups patients undergoing ECPR initially had significantly higher APACHE II scores ( P =0.03), increased norepinephrine dosages ( P =0.03) and elevated levels of creatine kinase ( P <0.0001), creatinine ( P =0.04) and lactate ( P =0.02) before cardiopulmonary resuscitation compared with those undergoing CCPR. After equalising these parameters significant differences were observed in short and long-term survival, favouring ECPR over CCPR (27% vs. 17%; P =0.01 (short-term) and 23.1% vs. 11.5%; P =0.008 (long-term); median follow-up duration after discharge 1136 days (interquartile range 823–1416)). There was no significant difference in the incidence of a cerebral performance categories score of 1 or 2 between the matched groups (CCPR 66.7% vs. ECPR 83.3%; P =0.77). ECLS implantation was the only significant and independent predictor of mortality in multivariate Cox regression analysis (hazard ratio 0.57, 95% confidence interval 0.35–0.90; P =0.02). Conclusion: In our cohort of cardiovascular patients ECPR was associated with better short- and long-term survival over CCPR, with a good neurological outcome in the majority of the patients with refractory in-hospital cardiac arrest.